Comparative Analysis of the Effect Dual Spark Ignition and Single Spark Ignition on Performance and Exhaust Emissions in Bioethanol-Fueled Engines - Permanasari, Avita Ayu; Wahidin, Ahmad Faizal; Ismail, Hasan; Komara, Erwin; Puspitasari, Poppy; Lorenzo, Gina A. (Journal of Mechanical Engineering Science and Technology (JMEST), 2024)
Bioethanol is an alternative fuel that has a high octane value of around 100 to 110, making it difficult to be applied to spark ignition engines directly. So, it is necessary to make adjustments, including increasing combustion efficiency and thermal efficiency of the combustion chamber by increasing the compression ratio and adjusting the ignition system, both in single spark ignition (SSI) and dual spark ignition (DSI) types. The study aims to determine the effect of SSI and DSI applications on engine performance, specific fuel consumption (SFC), and exhaust emissions using 96% and 99% levels of bioethanol fuel. The results showed that, in general, there was an increase in power, torque, and thermal efficiency as well as a decrease in emissions and better SFC in the DSI engine compared to the SSI engine with 99% bioethanol fuel. The highest power was obtained at 6.89 HP or 5.6% higher than the SSI engine, and peak torque was obtained by 14.95 N.m at 6500 rpm on the DSI engine using 99% bioethanol. Meanwhile, the minimum SFC reduction was obtained at 13.87% lower than that of DSI. The highest thermal efficiency of the DSI engine occurs at 7000 rpm, which is 38.19% when using 96% bioethanol. NOx emission increased when using 99% bioethanol on the DSI engine by 15.58% compared to the SSI engine. CO emissions decreased by 72.51% in the DSI engine with 96% bioethanol fuel. At the same time, CO2 experienced the highest decrease of 76.92% at 5500 rpm on 99% bioethanol DSI engine.